Self-perception regarding dental aesthetics, knowledge and attitude of traumatic dental injury and halitosis among people of Aurabani, Sunsari district of Eastern Nepal - Dahal, S; Agrawal, SK; Shrestha, A; Bhagat, TK (Journal of College of Medical Sciences-Nepal, 2015)
Background and Objectives: Increased concern over dental appearance has been observed during childhood and adolescence to early adulthood. The study was conducted with objectives to assess the self-perception of dental aesthetics, knowledge, attitude and management of dental trauma and halitosis. Materials and Methods: Self-administered questionnaire translated in Nepali language consisting of 32 questions was used. The completed questionnaires were analyzed using descriptive statistics. Results: Out of the total study population, 63% were satisfied with their overall tooth appearance and 71.7% with their tooth color. Twenty-nine percent had experienced dental trauma. More than half of the study population thought that immediate treatment was required after dental trauma. Fifty seven percent of the villagers had halitosis. Conclusion: The research clearly shows that the people of Aurabani VDC were satisfied with their tooth color and overall tooth appearance; however the knowledge regarding emergency management of dental trauma, the cause and management of halitosis was insufficient. JCMS Nepal. 2015;11(1):6-8